Efeito do tratamento periodontal não cirúrgico em indivíduos com artrite reumatóide e periodontite: aspectos epidemiológicos, clínicos, microbiológicos e biomarcadores - Marcela De Faria Moura (2020)
Objectives: Current evidence recognizes that periodontitis (PE) and rheumatoid arthritis (RA) share common risk factors and some similar pathophysiological pathways, such as chronic inflammation induced by pro-inflammatory cytokines and destruction of connective and bone tissues. Thus, this thesis presents four studies of the possible association between PE and RA with the following objectives: to assess the periodontal condition, severity and extent of periodontitis and the clinical and epidemiological aspects of its association with RA. To investigate the influence of non-surgical periodontal treatment (TPNS) on the periodontal clinical parameters, bacterial levels of A. actinomycetemcomitans, P. gingivalis, T. forsythia, T dentic and the activity of RA (DAS28). In addition to quantify blood and salivary levels of the biomarkers RANKL, OPG, RANKL / OPG, Survivina, and cyclic citrullinated anti-peptide antibodies (ACPAs) and anti-carbamylates (Anti-CarP). Methods: The study sample consisted of a total of 471 individuals randomly divided into groups, according to the objective of each study. The clinical trial performed the following assessments at baseline (T1) and 45 days (T2) after TPNC: periodontal examinations of full mouth, microbiological analysis using real-time qPCR, assessments of the Disease Activity Score (DAS-28). In addition, the quantification of biomarkers and Anti-Carp antibodies and ACPAs performed by ELISA in serum / saliva. Results: The present study reported a high prevalence of PE in individuals with RA and an important association between the occurrence, severity and extent of PE associated with RA and smoking. The non-surgical periodontal treatment was effective in improving the clinical periodontal condition, reduced the presence of the periodontal pathogens evaluated and improved the clinical picture of RA (reduced DAS-28 scores). Additionally, it reduced the levels of survivin, RANKL and concentration of ACPAs and Anti-CarP. Conclusion: Our findings corroborate the robustness of the scientific evidence on the association between periodontitis and RA. Thus, the control of periodontal infection in patients with RA and PE can be an important therapeutic tool in the control of RA